TISSUE CULTURE OPTIMIZATION OF PODOPHYLLUM HEXANDRUM L., AN ENDANGERED MEDICINAL PLANT - Z. Zuhra; D. Saleem; W. Akhtar; T. Mahmood1 (Journal of Animal and Plant Sciences, 2020)
hexandrum (Bankhakri) is an important medicinal plant due to its useful active compounds such as podophyllotoxin, a precursor of anti-cancer drugs. Currently, it is carrying the status of endangered species in Pakistan, India, China and Afghanistan due to slow growth and overharvesting. The present study is an attempt to establish an efficient protocol for callogenesis and organogenesis of P. hexandrum. Fresh fruits and rhizomes were collected from natural habitats. Seeds were sterilized and germinated for callogenesis and organogenesis. The present study describes that leaf explants resulted in the highest callus response (100%) followed by stem (90%) on Murashige and Skoog media (MS) media supplemented with 6.75 µM Naphthalene acetic acid (NAA) and 11.37 µM 6-Benzylaminopurine (BAP). Moreover, 1.0 µM indole acetic acid (IAA) in combination with 5.0 µM BAP successfully induced 80% callogenesis from root explants while 2,4 Dichloro-phenoxy acetic acid (2,4-D) at 3.0 and 4.0 µM resulted in 20% calli from embryos. Principal component analysis (PCA) showed that leaf and stem explants revealed considerable callus response in combination of NAA+BAP. Rhizome did not support callogenesis rather direct shooting was achieved with a combination of IAA (10.42-11.42 µM) and activated charcoal 5 g/L. ANOVA showed the most significant variability (P = 0.007198) from rhizome explant in direct regeneration.
Keywords: Podophyllum hexandrum L.; Tissue culture; Conservation; Callogenesis; Organogenesis